Asia's Contribution to Global Rebalancing - Charles Adams; Hoe Yun Jeong; Cyn-Young Park (Asian Development Bank (ADB), 2010)
Developing Asia remains at the core of global payment imbalances. While the geographical concentration of current account imbalances is rather significant, with the People's Republic of China accounting for the lion's share of the region's current account surplus, how Asia contributes to global rebalancing also depends critically on the NIEs and larger ASEAN economies. Given the region's huge diversity, the necessary national macroeconomic and structural policies will vary significantly across Asia's emerging economies. Whereas near-term rebalancing efforts will be driven primarily by macroeconomic and exchange rate policies, medium- to long-term measures will involve policies and structural reforms directed to boost domestic and regional demand as a source of economic growth. In this paper, we argue that regional rebalancing will depend critically on the adoption of deeper and more comprehensive structural reforms and further trade liberalization that promote domestic spending—thus reducing Asia's high dependence on extra regional demand. Priority policies should include infrastructure spending, competition, trade, financial development, investment, immigration, and other social policies to reduce national savings.
hdl:11540/1944
Keywords: E61; F42; F43; 330; global imbalances; Asia; rebalancing